Cemaran angka kuman pada saus cabai pedagang pentol kuah di Jalan Daya Nasional - Maulidiyah Salim; Jajar Pramata Syari; Laila Kamilla; Anisa Fitri Midani (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2020)
Chili sauce is a food additive made from chili which is processed from the processing of chili that is cooked and of good quality with the addition of other ingredients. There is a chili sauce in the form of packaging and processed home industry, the use of chili sauce in the community is often presented as a supplement to a variety of foods. However, the cleanliness of chili sauce still needs to be questioned considering the factors that can affect the contamination of chili sauce can be obtained from processing, serving and contamination from the surrounding environment. This study aims to determine the number of bacteria in the chili sauce in meatball traders on daya nasional street. The research design used is descriptive. The sampling technique in this study was by total sampling. The research method used is the Total Plate Count (TPC) method. The number of samples taken in this study amounted to 8 samples. Based on the results of the study, the highest number of germs is 2x106 colonies / gr and the lowest is 3.4x104 colonies/gr, it can be concluded that the entire sample in this study did not meet the conditions set out in Standar Nasional Indonesia (SNI) about chili souce No. 7388 in 2009 which is a maximum of 1x104 colonies/gr.